Дослідження автоматизованого електрообладнання для дозування подрібнених коренебульбоплодів - Рамш, В. Ю.; Шаршонь, В. Л. (Energy and Automation, 2017)
RESEARCH OF THE AUTOMATED ELECTRICAL EQUIPMENT FOR THE DOSAGE OF THE GROUND UP ROOT GARDEN-STUFFS V. Y. Ramsh, V. L. Sharshon Productive experience in our country and data of leading research institutes showed that the use for feeding of pigs of the ground up juicily-green forage considerably improved the biological value of forage mixtures and abbreviates the expense of the concentrated forage in middle on 35-40 %. However the electrical equipment of the modern grinding down of forage and their analogues in industry does not give an opportunity to provide the necessary mode of preparation of feed mixture. Most perspective for the construction of the systems of automatic control, as the conducted analysis showed, there is a super-high-frequency method of measuring, that in a most measure can provide wide functional possibilities and satisfactory metrology descriptions of measuring device of charges simultaneously, next to acceptable complication will both build on and his exploitations in an agricultural production. A basic task in such terms is minimization of dispersion of error of stabilizing of expense of initial stream of the ground up forage at maintenance of the productivity of grinding down at optimal level, that, in turn, results also in stabilizing of loading of electric occasion of grinding down aggregate. It will allow next to providing of the optimal productivity of grinding down to redistribute considerable part of the dynamic loading on the powerful electric occasion of grinding down on a less power-hungry occasion loading to auger. Thus, simultaneously the productivity rises and the specific power-hungryness of grinding down goes down. For research of the automated electrical equipment of dosage of the ground up root garden-stuffs modernized setting of IКС-5М. Expense of forage measured by the super-high-frequency measuring device of charges on the exit of grinding down. A signal from the measuring device of charges enters device of comparison of frequency regulator, that produces signals management asynchronous engine that changes the rate of movement of auger, accordingly and serve of root garden-stuffs on a grinding down drum. It is set that optimal frequencies of measuring device of charges of rich fodders fold f1=3 GHz and f2=24 GHz, powers of super-high-frequency generator equal Р1=of 100 mW, Р2= of 50 mW, and corner of sounding of stream of feed by Doppler radar αd=40°±5°. Researches of super-high-frequency measuring device of charges showed that the error of measuring of expense of the ground up rich fodders in a continuous stream did not exceed 3-7 %. The worked out electrical equipment provides stabilizing at set level of expense of forage and current of electric motor drains with an unevenness that does not exceed 15 % after the coefficient of variation. It gives an opportunity to promote on a 15 - 25 % productivity and accordingly to bring down the power specific-capacitance of growing of root garden-stuffs shallow on 15 - 25 %.